Analisis Faktor-faktor yang Memengaruhi Penyaluran Kredit pada Bank Konvensional Periode 2015-2019 - Rurun Ayu Anggraini (Jurnal Ilmu Manajemen, 2021)
Lending to conventional banks is an activity that will generate profits for the banks, and with credit, it can improve the welfare of people in a country. The purpose of this study is to determine the effect of Third Party Funds (TPF), Capital Adequacy Ratio (CAR), Return on Assets (ROA), Non Performing Loans (NPL), and Loan to Deposit Ratio (LDR) on credit disbursement at conventional banks period year 2015-2019. This study uses quantitative data types with associative methods. The sample is 24 banks with a purposive sampling method. The data analysis technique used is multiple linear regression using the SPSS software application. The results show that TPF and LDR had a positive and significant effect on lending. CAR, ROA, and NPL did not affect distribution credit. However, simultaneously the independent variables affect the dependent variable (credit distribution). Banks as providers of funds must pay attention to the factors that influence lending so that both banks, users of funds, and the government can benefit from the provision of these funds.